Firm-worker matching in industrial clusters - Octávio Figueiredo; Paulo Guimaraes; Douglas Woodward (Institute for the Study of Labor (IZA), 2011)
In this paper we use a novel approach and a large Portuguese employer-employee panel data set to study the hypothesis that industrial agglomeration improves the quality of the firm-worker matching process. Our method makes use of recent developments in the estimation and analysis of models with high-dimensional fixed effects. Using wage regressions with controls for multiple sources of observed and unobserved heterogeneity we find little evidence that the quality of matching increases with firm's clustering within the same industry. This result supports Freedman's (2008) analysis using U.S. data.
urn:nbn:de:101:1-201110263548
Keywords: R12; R39; J31; 330; agglomeration; matching; fixed-effects; Regionale Konzentration; Branche; Arbeitsnachfrage; Arbeitsangebot; Matching; Schätzung; Portugal